The Effects of Horizontal Gene Transfer on the Evolution of Land Plants - Jandron, Memphis C (East Carolina University, 2023)
This study sought to understand how horizontal gene transfer (HGT) has affected the evolution of land plants. Land plants evolved from charophyte green algae. A list of candidate genes derived from HGT was generated from the genome of the charophyte green alga Chlorokybus atmophyticus and were subjected to detailed phylogenetic analyses to investigate their evolutionary origin. The flowering plant Arabidopsis thaliana was used as a reference organism to understand the functions of the investigated genes, which in turn were used to assess the contribution of acquired genes to the evolution and adaptation of plants. I performed a detailed investigation on three acquired genes, including Chrsp45S09062 in the cupredoxin superfamily that encodes a multicopper oxidase protein, Chrsp52S06587 that encodes a calcium-dependent phosphotriesterase superfamily protein, and Chrsp22S08802 that encodes a protein with histidine kinase 1 activity. BLASTP searches were performed against the NCBI non-redundant protein sequence database using the HGT candidate genes from C. atmophyticus. Identified homologs were sampled for each candidate gene from representative groups of both prokaryotes and eukaryotes and then input into the computer program MEGA to perform a multiple sequence alignment (MSA). A phylogenetic tree was generated for each gene using MEGA and the resulting MSA. The phylogenetic trees generated were analyzed to identify true cases of HGT, and biochemical functions and related biological processes were further researched on each acquired gene to determine the effects of HGT on plant evolution. In the evolution of plants, the expected impact of HGT is a mechanism that aids in the exchange of genetic information to benefit the adaptation of land plants to their environment.
Keywords: Evolution; Horizontal gene transfer